The mirror mode: a “superconducting” space plasma analogue - R. A. Treumann; W. Baumjohann (Annales Geophysicae, 2018)
We examine the physics of the magnetic mirror mode in its final state of saturation, the thermodynamic equilibrium, to demonstrate that the mirror mode is the analogue of a superconducting effect in a classical anisotropic-pressure space plasma. Two different spatial scales are identified which control the behaviour of its evolution. These are the ion inertial scale λim(τ) based on the excess density Nm(τ) generated in the mirror mode, and the Debye scale λD(τ). The Debye length plays the role of the correlation length in superconductivity. Their dependence on the temperature ratio τ = T‖∕T⟂ < 1 is given, with T⟂ the reference temperature at the critical magnetic field. The mirror-mode equilibrium structure under saturation is determined by the Landau–Ginzburg ratio κD = λim∕λD, or κρ = λim∕ρ, depending on whether the Debye length or the thermal-ion gyroradius ρ – or possibly also an undefined turbulent correlation length ℓturb – serve as correlation lengths. Since in all space plasmas κD ≫ 1, plasmas with λD as the relevant correlation length always behave like type II superconductors, naturally giving rise to chains of local depletions of the magnetic field of the kind observed in the mirror mode. In this way they would provide the plasma with a short-scale magnetic bubble texture. The problem becomes more subtle when ρ is taken as correlation length. In this case the evolution of mirror modes is more restricted. Their existence as chains or trains of larger-scale mirror bubbles implies that another threshold, VA > υ⟂th, is exceeded. Finally, in case the correlation length ℓturb instead results from low-frequency magnetic/magnetohydrodynamic turbulence, the observation of mirror bubbles and the measurement of their spatial scales sets an upper limit on the turbulent correlation length. This might be important in the study of magnetic turbulence in plasmas.